Factors associated with timely COVID-19 vaccination in a population-based cohort of patients with cancer. (2nd November 2022) - Powis, Melanie; Sutradhar, Rinku; Patrikar, Aditi; Cheung, Matthew; Gong, Inna; Vijenthira, Abi; Hicks, Lisa K; Wilton, Drew; Krzyzanowska, Monika K; Singh, Simron
Abstract: Background: In many jurisdictions, cancer patients were prioritized for COVID-19 vaccination because of increased risk of infection and death. To understand sociodemographic disparities that affected timely receipt of COVID-19 vaccination among cancer patients, we undertook a population-based study in Ontario, Canada. Methods: Patients older than 18 years and diagnosed with cancer January 2010 to September 2020 were identified using administrative data; vaccination administration was captured between approval (December 2020) up to February 2022. Factors associated with time to vaccination were evaluated using multivariable Cox proportional hazards regression. Results: The cohort consisted of 356 535 patients, the majority of whom had solid tumor cancers (85.9%) and were not on active treatment (74.1%); 86.8% had received at least 2 doses. The rate of vaccination was 25% lower in recent (hazard ratio [HR] = 0.74, 95% confidence interval [CI] = 0.72 to 0.76) and nonrecent immigrants (HR = 0.80, 95% CI = 0.79 to 0.81). A greater proportion of unvaccinated patients were from neighborhoods with a high concentration of new immigrants or self-reported members of racialized groups (26.0% vs 21.3%, standardized difference = 0.111, P < .001), residential instability (27.1% vs 23.0%, standardized difference = 0.094, P < .001), or material deprivation (22.1% vs 16.8%, standardized difference = 0.134, P < .001) and low socioeconomic status (20.9% vs 16.0%, standardized difference = 0.041, P < .001). The rate of vaccination was 20% lower in patients from neighborhoods with the lowest socioeconomic status (HR = 0.82, 95% CI = 0.81 to 0.84) and highest material deprivation (HR = 0.80, 95% CI = 0.78 to 0.81) relative to those in more advantaged neighborhoods. Conclusions: Despite funding of vaccines and prioritization of high-risk populations, marginalized patients were less likely to be vaccinated. Differences are likely due to the interplay between systemic barriers to access and cultural or social influences affecting uptake.